The Cooperative Principle Analysis in About Time Movie - Yenny Widya Sari; Afriana Afriana (Linguistic, English Education and Art (LEEA) Journal, 2020)
This research had aimed to analyze cooperative principle by observing the characters’ utterances in About Time movie. A descriptive qualitative method was used in analyzing the data because it would be explained by words, phrases, and sentences. The data would be based on the characters’ utterances in About Time movie. In collecting the data, the researcher used the observational method and non-participatory, note-taking techniques. Pragmatic identity method was applied in analyzing the data. The result findings showed that all four maxims in cooperative principle were found through the utterances in About Time movie. The researcher found 37 data of maxims. The result indicated that there were 14 (38%) data maxim of quantity, 14 (38%) data maxim of relation, 7 (19%) data maxim of quality and 2 (5%) data maxim of manner. In summary, the most frequently data were found in the maxim of quantity and maxim of relation. The least data were found in maxim of manner. Keywords: Cooperative Principle, Maxims, Utterances, Movie